Orobanche (Orobanche spp.) in Lentil (Lens culinaris Medic.); How Much Losses by Yield, Quality, Marketing Prices and Profitability? - Sirac, Yolcu; Özberk, İrfan and Özberk, fethiye (Journal of Agricultural Sciences (Belgrade), 2020)
This research aimed to inspect the impacts of severe parasitic plants (Orobachee spp.) on to grain yield, some quality characteristics, marketing price and profitability loss of red lentil in the major lentil growing area of South-east Anatolia. Farmer field trials were carried out in two neighboring fields planted with Yerli kırmızı (landrace) and Firat-87 varieties of lentil employing split plot experimental design inYollarbasi location of Viransehir in 2018-19 crop growing season. Lentil varieties placed into main plots and the broomrape infestations (i.e.0, 5, 10, and 15 plants m-2) in the subplots respectively. Grain yield, hectoliter weights and 1000 kernel weights and protein contents (%) were scored. All grain samples were presented to randomly chosen grain purchasers in local commodity market and marketing price offers were scored respectively. Results showed that broomrape infestation from zero to15 broomrapes m-2 reduced the grain yield from 2033, 33 kg ha-1 to 833, 33 kg ha-1 with 59 % significantly. Although being non-significant, Firat-87 (1512, 5 kg ha-1) was found to be higher yielding than Yerli Kırmızı (1325 kg ha1). Regression equations between grain yield reductions vs. broomrape infestation ratios turned out to be significant and reliable with high coefficients of determinations for both varieties. Some visual purchasing criteria such as hectoliter and 1000 kernel weights were not affected seriously. Purchasers offered very similar marketing prices for pulse grains with all severity levels. Economic loss was huge (555 ha-1).It was concluded that regression equations derived from grain yield vs. infestation densities were found to be reliable with high coefficients of determinations and can be perfectly used for yield estimates under various levels of broomrape infestations